Self-identification of regional mass media - Kononova, Elena I. (Journal of the Belarusian State University. Journalism, 2021)
The article analyses the mass media of the Republic of Belarus, which are regional by type and geographical distribution. There are the typological characteristics of regional mass media, which allow us to determine their place in the national media system. The Belarusian experience shows that the modern communication environment changes the traditional approaches to determining the typology and offers new characteristics and functionality of mass media. Based on practical analysis, it is proved that regional information is becoming more important on a national scale, so editorial offices need changes in the organisation of technological and creative processes. This is the main thesis of the article, which is supported by recommendations. When forming the concept of a print or broadcast media, it is necessary to clearly navigate the coordinate system of the typological definition and functional affiliation in the media system, as well as to review self-identification, identify the main and secondary tasks, and correlate the concept of media with internal and external conditions of functioning. Representatives of regional mass media should clearly understand their purpose and role. Self-identification will show a practical result of optimising the work of the regional mass media and a higher efficiency of information activity on the sustainable development of the regions.